Pengaruh Pembelajaran Model Hybrid Learning Terhadap Hasil Belajar Siswa Kelas XI pada Mata Pelajaran Fiqih Mawaris di MAN 9 Jombang - Kris Yuan Hidayatulloh, Muhammad; Wati, Nur Rohmah (JoEMS (Journal of Education and Management Studies), 2023)
The purpose of this study was to examine whether or not the effect of hybrid learning model lerning on student learning outcomes in class XI MAN Jombang. The research method used is an experimental method with a One-Shot Case Study design. The sample used in theis study were students of class XI MIA 1 Man 9 Jombang, totaling 43 students who were teken using purposive sampling technique. The data analysis technique learning used is the one sample “t” test with a significance level of 5% (0.05). the results showed that the hybrid llearning model had a significant effect on student learning outcomes in Fiqh subjects, as evidenced by a one-sample t-test analysis with the results of of t-count > t-table (9.168 > 1.684) and sig. (2-tailed) of 0.000 or < 0.05.